Talkitt: toward a new instrument based on artificial intelligence for augmentative and alternative communication in children with down syndrome - Costanzo, Floriana; Fucà, Elisa; Caciolo, Cristina; Ruà, Deborah; Smolley, Sara; Weissberg, Danny; Vicari, Stefano (Frontiers in Psychology, 2023)
Individuals with Down syndrome (DS) often exhibit a severe speech impairment, with important consequences on language intelligibility. For these cases, the use of Augmentative Alternative Communication instruments, that increase an individual’s communication abilities, becomes crucial. Talkitt is a mobile application created by Voiceitt Company, exploiting speech recognition technology and artificial intelligence models to translate in real-time unintelligible sounds into clear words, allowing individuals with language production impairment to verbally communicate in real-time. A final number of twenty-three individuals with DS, aged 5.54 to 28.9 years, participated in this study and completed six months of training. The application was trained to consistently recognize at least 20 different unintelligible words (e.g., nouns and/or short phrases)/person. The goal of the study was to evaluate the usability and satisfaction related to the application use as well as the effects of the use of the Talkitt application on adapted behavior and communication of the participants. Results revealed good usability and high levels of satisfaction related to the application use. Moreover, we registered the improvement in linguistic abilities, particularly naming, which paves the road for a potential role of Talkitt as a supportive and rehabilitative tool for DS.